Images: The piano music of Claude Debussy - Roberts, Paul (Portland, Oregon Amadeus Press, 1996)
Paris at the turn of the 20th century was obsessed with the interrelations of the arts. It was a time when artists and writers spoke of poetry as music, sounds as colors, and paintings as symphonies. The music of Claude Debussy, with its unique textures and dazzling colors, was the perfect counterpart to the bold new styles of painting in France. Paul Roberts probes the sources of Debussy's artistic inspiration, relating the "impressionist" titles to the artistic and literary ferment of the time. He also draws on his own performing experience to touch on all the principal technical problems for a performer of Debussy's piano music. His many suggestions about interpreting the music will be particularly valuable to performers as well as listeners.